SISTEM PENUNJANG KEPUTUSAN PEMILIHAN LAHAN TANAM JAGUNG DI KELOMPOK TANI DEWI - Prasetyan, Andri; Prasetyo, Andri (DINAMIKA DOTCOM, 2016)
Farmers Group Dewi Ratih III is an institution that is engaged in agriculture in the villageSukoanyar district. Pakis District. Malang . Farmers Group III Dewi Ratih always do things thatwill encourage people to perform in a way that modern agriculture so that the results can byfarmers is increasing . In the selection of decision making corn planted area farmer groups DewiRatih III is currently using the system manually decisions that process data area of land that willbe planting corn by meeting with members of the group and head of the group that will take a longtime and inaccurate .Â The method used is a data collection and system development . Data collection methods used wereinterviews and surveys . System development method used is Simple Additive Weighting ( SAW)Support systems keputsan election corn planted area is capable menggolah land data withoutholding a meeting with all members of farmer groups . This system can perform the dataperhitunggan corn planted area accurately .Inventory Information System is running on Windows 7 by using RDMS MySQL 5.6 and MySQLusing Connector ADO.net .Keywords : Systems , Support , Decision , Election , Land